2012
DOI: 10.1139/x2012-004
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of enhanced nitrogen deposition and soil acidification on biomass production and nitrogen leaching in Chinese fir plantations

Abstract: Atmospheric pollution levels in China are increasing quickly. Experience from other polluted regions shows that tree growth could be affected, but long-term effects of N deposition and soil acidification on Chinese forests remain mostly unknown. Soil acidification and N deposition were simulated for Chinese fir (Cunninghamia lanceolata (Lamb.) Hook.) plantations managed for three consecutive 20-year rotations in southeastern China. A factorial experiment combined four rain pH levels (2.5, 4.0, 5.6, and 7.0), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…This situation benefits camphor laurels as it reduces N losses from the ecosystem, particularly at the beginning of the rotation when camphor laurels are small and do not capture and use most of the available N. Later, when ash declines and leaf and woody litter decompose, such nutrients are released and can be used by camphor laurel trees. Similar mechanisms to reduce nutrient losses from the ecosystems have been reported before for Chinese sub-tropical forests [28,[31][32][33]. In addition, stand litter production increases in mixed forests, a phenomenon reported before [63].…”
Section: Interspecific Competition and Facilitation Processessupporting
confidence: 77%
See 1 more Smart Citation
“…This situation benefits camphor laurels as it reduces N losses from the ecosystem, particularly at the beginning of the rotation when camphor laurels are small and do not capture and use most of the available N. Later, when ash declines and leaf and woody litter decompose, such nutrients are released and can be used by camphor laurel trees. Similar mechanisms to reduce nutrient losses from the ecosystems have been reported before for Chinese sub-tropical forests [28,[31][32][33]. In addition, stand litter production increases in mixed forests, a phenomenon reported before [63].…”
Section: Interspecific Competition and Facilitation Processessupporting
confidence: 77%
“…Among them, the model FORECAST [20] stands out, as it has been used as a management evaluation tool in many types of forest ecosystems around the world [21][22][23][24][25][26][27], including tropical and sub-tropical forests [28][29][30][31][32][33]. The model is specially designed to examine the impacts of different management strategies at the ecosystem level, accounting for resource competition (intra-and inter-specific) when several species (trees and understory) are present in the same stand, including natural and planted mixedwoods [34,35].…”
Section: Restoring the Resilience Of Reforested Areasmentioning
confidence: 99%
“…As for nitrogen in the soil, nitrate leaching could contribute to the loss of total nitrogen under the simulated acid rain. Previous studies have demonstrated that the high concentrations of base cations or H + in throughfall may result in the loss of soil nitrogen through leaching (Blanco et al, 2012;Xu et al, 2015). Additionally, it was reported that acid rain could inhibit nitrogen mineralization, and thus reduce NH + 4 -N supply (Ouyang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The mean annual frost-free period is 270 days, with average annual sunshine time of 1860 h. Soils are predomin antly red earths and yellow-red soils (lateritic clay-domina ted Ferrisoils) with textures ranging from light to medium loam and pH from 4.7 to 5.2. In this warm and humid subtropical monsoon climate with nutrient-poor soils, N is usually the growth-l imiting factor Blanco et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, the model FORECAST (Kimmins et al, 1999 ) stands out. It has been used as a management evaluation tool in many types of forest ecosystems around the world (Sachs and Sollins, 1986;Wang et al, 1995;Morris et al, 1997;Wei et al, 2000Wei et al, , 2003Blanco et al, 2007;Seely et al, 2010 ), including tropical and subtropical forests (Bi et al, 2007;Blanco and González, 2010a,b;Xin et al, 2011;Blanco et al, 2012;Wei et al, 2012 ). The model was specifically designed to examine the impacts of different managemen t strategie s or natural disturbance regimes on long-term site productivity and forest carbon sequestratio n. A detailed description of the FORECAST model can be found in Kimmins et al (1999Kimmins et al ( , 2010 and a brief description of the algorithms simulating C sequestra tion will be presented in the next section.…”
Section: Introductionmentioning
confidence: 99%